2012
DOI: 10.5694/mja11.10856
|View full text |Cite
|
Sign up to set email alerts
|

Shared care for chronic eye diseases: perspectives of ophthalmologists, optometrists and patients

Abstract: Shared care between local optometrists and hospital-based ophthalmologists can help to reduce patient waiting time for review and offers an opportunity for these two groups of eye care professionals to collaborate in providing localised care for the benefit of patients. However, trust and relationship building need to be further developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
68
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(76 citation statements)
references
References 13 publications
6
68
0
Order By: Relevance
“…Shared care schemes are also attractive to patients who would find it more convenient to be monitored closer to their home. 34,35 In line with previous research, the service users described how they were frustrated at the lack of support and information that they had received about their condition. 36,37 Consequently, they felt that being monitored in the community would enable them to build up a relationship with one optometrist, with whom there would be more of an opportunity to receive better support and information.…”
Section: Views Of Patients and Health Professionals About The Shared supporting
confidence: 64%
See 4 more Smart Citations
“…Shared care schemes are also attractive to patients who would find it more convenient to be monitored closer to their home. 34,35 In line with previous research, the service users described how they were frustrated at the lack of support and information that they had received about their condition. 36,37 Consequently, they felt that being monitored in the community would enable them to build up a relationship with one optometrist, with whom there would be more of an opportunity to receive better support and information.…”
Section: Views Of Patients and Health Professionals About The Shared supporting
confidence: 64%
“…Shared care research for a variety of eye conditions has reported that, although web-based training is a convenient and effective option, it is not representative of clinical practice and may not be appropriate for teaching practical clinical skills which need to be developed through attendance at a training course. 35,41 Health professionals in the current study also highlighted that face-to-face training of this kind would provide reassurance to the ophthalmologists that optometrists were being trained to a high standard and further encourage interprofessional collaboration.…”
Section: Views Of Patients and Health Professionals About The Shared mentioning
confidence: 86%
See 3 more Smart Citations